Wind Power in Spain: Potential and Consequences - Campos Revuelta, Andrés (Papeles de Europa, 2011)
This paper analyzes the situation of the Spanish wind power industry, trying to discern how the renewable energy, and among them wind power, should be part, from an economic standpoint, of the energy change that Spain should undertake without delay, and the implications that would result, both positive and negative. To do this, we start with the shortcomings of the Spanish energy sector and we establish criteria under which the policy makers should develop the new energy mix. We conclude by explaining the need for change, the current energy mix and the way of pricing power.